Mental poker - Šāmîr, ʿAdî; Rivest, Ronald L.; Adleman, Leonard 1945- (Massachusetts Inst. of Technology, Lab. for Computer Science, 1979)
Is it possible to play a fair game of 'Mental Poker'. We will give a complete (but paradoxical) answer to this question. We will first prove that the problem is intrinsically insoluble, and then describe a fair method of playing 'Mental Poker'. (Author).
Keywords: Algorithms; Computations; Cryptography; Gambling; Game theory; Logarithm functions; Non-radio Communications; Problem solving; Theoretical Mathematics; Spieltheorie; Kryptologie